Fiscal Correction Analysis of Commercial Loss Profit Report in Determining the Income of Income Establishment at PT. Medan - Zulia Hanum (International Journal of Accounting & Finance in Asia Pasific (IJAFAP), 2019)
This study aims to determine how the application of tax accounting in accordance with applicable tax laws and to determine the calculation of income tax (VAT) in accordance with law No. 36 of 2008. This research is a qualitative research. This research was conducted at PT. Asam Jawa Medan. This study uses a qualitative research type with a descriptive approach. Descriptive qualitative research is intended to describe and describe the phenomena that exist, both natural and human engineering, which are more concerned about the characteristics, quality, interrelationships between activities. This research was conducted at PT. Asam Jawa Medan. Data collection techniques used in this study were documentation and interviews. Data analysis with descriptive method is to describe the state of the financial statements of the phenomena that occur by collecting data, carrying out fiscal corrections in accordance with Law No. 36/2008 and calculating the income tax payable. The type of data used is secondary data. Based on the results of the study note that PT. Asam Jawa has applied tax accounting in accordance with applicable tax regulations, but in the calculation of income tax (PPh) of PT. Tamarind is not in accordance with Law No. 36 of 2008. From the results of this study it is also known that PT. Tamarind in the Calculation of Income Tax (PPh) of PT. Tamarind is not yet in accordance with Law Number 36 of 2008.